PENGARUH MEDIA PEMBELAJARAN PHET SIMULATION TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN FISIKA KELAS XI DI SMA NEGERI 9 MAKASSAR - Putri Aulia Salam; Kasman; Wahyuddin (STKIP Subang, 2024)
Research on the Effect of phET Simulation Learning Media on Student Understanding in Physics Class XI at SMA Negeri 9 Makassar. This study aims to determine the effect of phet simulation learning media on student understanding of physics subjects in class XI at SMA Negeri 9 Makassar. The sample in this study was class XI students at SMA Negeri 9 Makassar which amounted to 36 students. Based on the results of research and data analysis regarding the comparison of statistical values, and comparison of student understanding categories has proven a positive influence on the understanding of students in class XI SMA Negeri 9 Makassar which can be seen from the results of student understanding through descriptive statistical analysis before using phET simulation learning media the average student score is still below the KKM value and after using phET simulation learning media the average student score increases above the KKM value. It is known that the value of the posttest results is 83 greater than the value of the pretest results which is 57. Furthermore, based on the results of the N-Gain test, a value of 77 is obtained which if rounded to 0.77 with a high category. Based on these results it can be concluded that there is a significant positive influence on student understanding. From the results of these data it can be concluded that through phET simulation learning media in learning can have a positive influence on student understanding in physics class XI SMA Negeri 9 Makassar.